The Effectiveness of Establishing a Homework Habit Through Ape "at Home" in Fostering Independence for Children Aged 5-6 Years - Rizqiyana, Nadya; Deni Widjayatri, RR. (Seulanga : Jurnal Pendidikan Anak, 2024)
This research aims to find out whether APE "Di Rumah" is effective in increasing the independence and development of children aged 5-6 years. Independence is very important because it can influence their development towards elementary school level. At this stage, children begin to show developmental maturity in social, emotional, and cognitive skills that are important for school. They begin to be able to handle themselves better, such as wearing clothes, helping with housework, and following simple instructions. Homework is often seen as a way to teach children to be more responsible. However, there are more benefits to this habit, especially in terms of training independence for children aged 5-6 years. Getting children aged 5-6 years old used to doing homework is an important step in preparing them for elementary school. Involving children in homework helps them build good habits, increasing children's independence skills. The method used in this research is through descriptive qualitative methods by collecting research results from APE "Di Rumah". Data collection was carried out through observation activities on early childhood children in Class B aged 5-6 years at the Kindergarten Lab School UPI Serang Campus. The data analysis technique was carried out using the Revised Bloom Operational Verb which was used as a research instrument. The research results show that APE "Di Rumah" is effective in supporting the independent development of children aged 5-6 years.